2011
DOI: 10.1016/j.ajog.2011.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Racial and regional differences in age at menopause in the United States: findings from the REasons for Geographic And Racial Differences in Stroke (REGARDS) study

Abstract: Objectives To examine regional and Black-White differences in mean age at self-reported menopause among community-dwelling women in the US. Study Design Cross-sectional survey conducted in the context of the REasons for Geographic And Racial Differences in Stroke and Myocardial Infarction study. Results We studied 22,484 menopausal women. After controlling for covariates, Southern women reported menopause 10.8 months earlier than Northeastern women, 8.4 months earlier than Midwestern women, and 6.0 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 26 publications
(44 reference statements)
5
47
2
1
Order By: Relevance
“…The direction of our results regarding parity is consistent with previous reports [5,20,24]. Incessant ovulation in nulliparity may be an important reason accounting for earlier onset of menopause.…”
Section: Variablessupporting
confidence: 94%
See 2 more Smart Citations
“…The direction of our results regarding parity is consistent with previous reports [5,20,24]. Incessant ovulation in nulliparity may be an important reason accounting for earlier onset of menopause.…”
Section: Variablessupporting
confidence: 94%
“…The SWAN (Study of Women's Health Across the Nation) suggested that the age at natural menopause was 51.4 years in a cohort study of 2247 women in a multiethnic sample of midlife women [5]. The present study showed that the overall median age of natural menopause was 50 years, which is similar to the McKnight's results [20] but earlier than the previously reported age of 50.6 [21]. Although menopause is a medical condition as a natural transition in the life cycle, it is very important for women to be aware of the adverse aspects of menopause, and prompted to seek prevention and treatment measures for their health.…”
Section: Variablessupporting
confidence: 93%
See 1 more Smart Citation
“…In a cross-sectional survey of 22,484 women, after controlling for covariates, it was noted that women from the Southern part of the United States reported menopause 10.8 months earlier than Northeastern women, 8.4 months earlier than midwestern women, and 6.0 months earlier than western women ( p <0.05) [ 38 ]. The cause for this effect is not known.…”
Section: North Americamentioning
confidence: 96%
“…McKnight et al [ 38 ] in 2011 found similar fi ndings to Gold in that no racial difference in age at menopause was shown between black and Caucasian women after covariates were controlled for in a crosssectional survey of 22,484 women in the United States [ 37 ]. A study of 17,070 women aged 35-55 years found African American women had earlier onset of natural menopause, and this was strongly associated with smoking and inversely associated with body mass index and oral contraceptive use [ 39 ].…”
Section: North Americamentioning
confidence: 97%